2021
DOI: 10.3390/ijms22042144
|View full text |Cite
|
Sign up to set email alerts
|

mTOR Signaling in Pulmonary Vascular Disease: Pathogenic Role and Therapeutic Target

Abstract: Pulmonary arterial hypertension (PAH) is a progressive and fatal disease without a cure. The exact pathogenic mechanisms of PAH are complex and poorly understood, yet a number of abnormally expressed genes and regulatory pathways contribute to sustained vasoconstriction and vascular remodeling of the distal pulmonary arteries. Mammalian target of rapamycin (mTOR) is one of the major signaling pathways implicated in regulating cell proliferation, migration, differentiation, and protein synthesis. Here we will d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 198 publications
2
28
0
Order By: Relevance
“…The PI3K/AKT/mTOR signaling cascade is a major signaling pathway involved in cell proliferation and protein synthesis in a variety of cell types including cancer cells and PASMCs ( Goncharov et al, 2014 ; Sahoo et al, 2016 ; Meng et al, 2017 ; Babicheva et al, 2021 ). Our lab and other investigators have reported that the PI3K/AKT1/mTORC1/C2 pathways are involved in the development and progression of experimental PH in mice ( Tang et al, 2015 , 2018b ; Goncharova et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The PI3K/AKT/mTOR signaling cascade is a major signaling pathway involved in cell proliferation and protein synthesis in a variety of cell types including cancer cells and PASMCs ( Goncharov et al, 2014 ; Sahoo et al, 2016 ; Meng et al, 2017 ; Babicheva et al, 2021 ). Our lab and other investigators have reported that the PI3K/AKT1/mTORC1/C2 pathways are involved in the development and progression of experimental PH in mice ( Tang et al, 2015 , 2018b ; Goncharova et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…The mTOR complex 1 (mTORC1) and mTORC2 play important roles in the regulation of cell proliferation and protein expression, while both complexes are involved in the development and progression of PH ( Houssaini et al, 2013 , 2016 ; Goncharov et al, 2014 ; Lee et al, 2016 ; Guo et al, 2019 ; Goncharova et al, 2020 ; Babicheva et al, 2021 ). PASMCs in the normal PA exhibit a differentiated, quiescent, and contractile phenotype.…”
Section: Resultsmentioning
confidence: 99%
“…Houssaini et al have reported that the proliferation of PASMCs derived from MCT-induced PAH rats was suppressed by rapamycin [ 22 ], an allosteric inhibitor of mTOR complex 1 [ 18 ]. Notably, restoring the mTOR pathway by upregulating phosphatase and tensin homolog, a regulator of mTOR [ 20 ], induces apoptosis in PASMCs [ 38 ]. In the present study, 10 μM H-1337M1 suppressed the activation of mTOR and the cell viability of hPASMCs at a level similar to that of LY294002, although the effects of 1 and 10 μM H-1337 and 1 μM H-1337 M1 on mTOR were moderate.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the mammalian target of rapamycin (mTOR) pathway has also been shown to be associated with PAH development. The activated mTOR pathway induces the proliferation of SMCs [ 18 , 19 ] and is associated with the development of vascular remodeling in PAH [ 20 ]. Moreover, the mTOR pathway is activated in experimental PAH animal models induced by hypoxia, MCT, and Su5416/hypoxia (Su/Hx) rat models, which are associated with the development of pulmonary vascular remodeling and right ventricle (RV) remodeling and dysfunction [ 21 , 22 , 23 ] Thus, activation of the ROCK and Akt/mTOR pathways plays important roles in PAH development, and inhibition of these pathways may be a new strategy for treating PAH.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation